THE CONCEPT OF "EARTH" IN THE HOLY BOOKS: THE BIBLE AND THE QUR'AN - Холикулова Юлдуз Шодиевна (Journals Park Publishing, 2025)
The concept of "Earth" occupies an important place in both sacred books — the Bible and the Koran. It not only designates the physical space where people live, but also has a deep spiritual and symbolic meaning. In this article, we will look at how the Earth is represented in these texts, its role in the divine plan, and man's relationship to this planet.
Keywords: God, Bible, Quran, holy books, Genesis, commandments, Promised Land, creation of the Earth, Earth and man.